Exploring the venous supply of the face: An illustrated overview of contemporary literature - Jeremy Isaac; Lee Walker; Stephen R. Ali; Iain S. Whitaker (JPRAS Open)
Understanding the vascular anatomy of the face is crucial for ensuring safe clinical practices, especially as aesthetic procedures involving hyaluronic acid fillers are gaining popularity. Although vascular complications from these procedures are rare, there has been a documented increase in adverse events linked to venous and arterial occlusions. This review addresses the knowledge gap regarding the facial venous system compared to the well-documented facial artery system, emphasising the importance of thorough anatomical knowledge to mitigate risks during injectable cosmetic procedures. The complex and variable anatomy of the facial veins, including connections to the intracerebral venous system, allows for the retrograde spread of infections and fillers, with key tributaries such as the angular and infraorbital veins facilitating communication with the cavernous sinus. Notably, the absence of valves in certain venous regions can lead to retrograde filler flow, exacerbating complications. This illustrated review provides an analysis of the facial venous anatomy, focusing on the distribution and depth of venous structures, and aims to equip practitioners with insights that can help reduce the incidence of vascular complications associated with cosmetic procedures.